Pengaruh Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Karyawan Kontrak PT ISS Indonesia Bintaro - Agam Aulia; Aris Ariyanto (Journal of Trends Economics and Accounting Research, 2021)
This study is to analyze the effect of training and work motivation at PT ISS Indonesia. The research method used is quantitative using primary data sourced from employee data at PT ISS Indonesia. The research test used classical assumption test, instrument test and data analysis used descriptive and verification analysis and the hypothesis test was t test and f test. The sampling technique used is a saturated sample with 100 respondents from all the population samples in this study. The results of the t-test that have been carried out, the number resulting from the training tcount (X1) is 7,160 and the motivation (X2) is 6.730, which means tcount > ttable (ttable is 2.70). Thus, H0 is rejected and H1 is accepted, which means that training has a partial (individual) effect on performance. Then from the results of the f test that has been carried out, the number resulting from fcount is 31.337, meaning that fcount > ftable (ftable of 2.70) meaning H0 is rejected and H1 is accepted, which means that there is a jointly significant influence between training and motivation on performance. The statistical results show that the effect of training (X1) on employee performance (Y) is 0.586 or 58.6%, while the influence between motivation and performance is 0.562 or 56.2%. The results showed that the training and work motivation of employees with the regression equation Y = 3.675 + 0.577 (X1) + 0.312 (X2). The results of the regression analysis showed that the training coefficient of 0.577 was positive and the motivation was 0.312.